2019
DOI: 10.3928/23258160-20191031-05
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescein Angiography Findings in Children With Congenital Zika Syndrome

Abstract: BACKGROUND AND OBJECTIVE: To evaluate the retinal and vasculature changes in infants with congenital Zika syndrome (CZS) using fluorescein angiography (FA). PATIENTS AND METHODS: This consecutive case series included six infants with CZS. FA and color fundus imaging were performed under general anesthesia in both eyes of all infants using a contact widefield digital imaging system. All color fundus images were obtained using a 130° field of view lens, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…In one study using OCT to examine retinal abnormalities, vessels appear very sparse and thin in some fundus photography images [ 33 ]. In another study using fluorescein angiography to evaluate retinal vasculature changes, diffuse avascularity of the peripheral retina, retinal vessels rectification, abnormal arteriovenous shunts, and vascular attenuation, leakage and tuft are observed [ 32 ]. These observations further support that our model is clinically relevant.…”
Section: Discussionmentioning
confidence: 99%
“…In one study using OCT to examine retinal abnormalities, vessels appear very sparse and thin in some fundus photography images [ 33 ]. In another study using fluorescein angiography to evaluate retinal vasculature changes, diffuse avascularity of the peripheral retina, retinal vessels rectification, abnormal arteriovenous shunts, and vascular attenuation, leakage and tuft are observed [ 32 ]. These observations further support that our model is clinically relevant.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7][8] Nevertheless, a recent study by Ventura and colleagues showed that fluorescein angiography (FA) performed using the RetCam III was capable of revealing in addition to the retinal vascular alterations, subtle retinal pigment epithelium changes, which were observed as window defects in the FA images and were misdiagnosed on fundus examination and color fundus photography using a wide-view lens. 17 In the present case series, we show that color fundus imaging using a magnification lens (80 field-of-view lens) is effective in revealing and documenting subtle macular changes in children with CZS.…”
Section: Introductionmentioning
confidence: 53%
“…Ventura et al showed another way of detecting these subtle macular changes by performing FA documentation in children with CZS and identifying window defects in apparently normal eyes. 17 In their case series, window defects were identified in 100% of studied eyes compared with 58% of eyes using wideangle imaging and fundus examination together. Similarly, the present study was also able to detect subtle macular changes in all studied eyes (100%) by performing high-magnification color images alone of children with CZS.…”
Section: Discussionmentioning
confidence: 99%